Meningkatkan Hasil Belajar Siswa Dengan Model Pembelajaran Cooperative Learning (CL) Pada Mata Pelajaran Matematika Kelas III SDN 4 Nyatang - Sonia, Sonia; Khoiri, Ahmad; Kartini, Kartini (STKIP Melawi, 2024)
Abstract: This research is based on the low student learning outcomes in mathematics learning in class III. The aim of the research is to determine the extent to which student learning outcomes have improved by using the cooperative learning model in mathematics subjects in class III at SDN 4 Nyatang. This study used the method Classroom Action Research. This type of research uses empirical classroom action research. The research subjects were 7 class III students at SDN 4 Nyang, consisting of 2 girls and 5 boys. The object of this research is student learning outcomes in mathematics learning using the cooperative learning model. Data collection techniques use tests, observation and documentation. The research instrument uses written tests and observation sheets. Data analysis techniques use test data analysis and learning implementation data analysis. The success criteria are if 85% of students' scores are above 65 (KKM). The results of research on improving student learning outcomes with cooperative learning learning model in mathematics in Class III SDN 4 Nyatang obtained learning outcomes in the first cycle of students who completed as many as 3 people or 42.85%. Then the learning outcomes in the second cycle of students who completed as many as 7 people or 100%. The results showed an increase in mathematics learning outcomes from cycle I to Cycle II by 57.15%. The conclusion of the study is the use of cooperative learning learning model can improve student learning outcomes. Keywords: Learning Outcomes, Cooperative Learning, Mathematics. Abstrak: Penelitian ini didasari oleh rendahnya hasil belajar siswa dalam pembelajaran matematika di kelas III. Tujuan penelitian untuk mengetahui sejauh mana peningkatan hasil belajar siswa dengan menggunakan model cooperative learning pada mata pelajaran matematika di kelas III SDN 4 Nyatang. Penelitian menggunakan metode Penelitian Tindakan Kelas. Jenis penelitian menggunakan penelitian tindakan kelas empiris. Subjek penelitian adalah siswa kelas III di SDN 4 Nyatang yang berjumlah 7 orang yang terdiri dari 2 orang perempuan, dan 5 orang laki-laki. Objek penelitian ini adalah hasil belajar siswa dalam pembelajaran matematika menggunakan model cooperative learning. Teknik pengumpulan data menggunakan tes, observasi dan dokumentasi. Instrumen penelitian mengunakan tes tertulis dan lembar observasi. Teknik analisis data menggunakan analisis data tes dan analisis data Keterlaksanaan pembelajaran. Kriteria keberhasilan apabila telah mencapai 85% nilai siswa di atas 65 (KKM). Hasil penelitian tentang meningkatkan hasil belajar siswa dengan model pembelajaran cooperative learning pada mata pelajaran matematika di kelas III SDN 4 Nyatang diperoleh hasil belajar pada siklus I siswa yang tuntas sebanyak 3 orang atau sebesar 42,85%. Kemudian hasil belajar pada siklus II siswa yang tuntas sebanyak 7 orang atau sebesar 100%. Hasil penelitian menunjukkan terjadi peningkatan hasil belajar matematika dari siklus I ke siklus II sebesar 57,15%. Kesimpulan penelitian adalah penggunaan model pembelajaran cooperative learning dapat meningkatkan hasil belajar siswa. Kata Kunci: Hasil Belajar, Cooperative Learning, Matematika.